Konsep Manajemen Kearsipan Dalam Prespektif Islam - Salimah Salimah; Ahmad Qurtubi; Machdum Bachtiar (Journal on Education, 2024)
This article discusses records management in an Islamic perspective, exploring the concepts and practices of records management in an Islamic perspective. This research explores the values, principles, and guidelines that form the foundation of records management in an Islamic context. The main focus of this research is on principles such as amanah (trust), fairness, honesty, and transparency applied in the management of documents and information. The purpose of this study is: to know the concept of archive management in an Islamic perspective, know the principles of archives, and know the importance of archiving. The research method used is qualitative, data collection is carried out using literature studies. Records management in an Islamic perspective is also explained as a collection of instruments that are stored systematically because they have a function so that whenever needed they can be found quickly and precisely so as to improve administrative services.